Foamed polypropylene beads and molded articles thereof

By introducing PTFE reinforcing agent into foamed polypropylene beads, physical entanglement is formed, which solves the problem of long molding cycle of EPP, achieves low energy consumption and short cycle molding effect, and improves the mechanical properties and appearance quality of EPP.

CN117050423BActive Publication Date: 2025-11-18WUXI HI TEC ENVIRONMENTAL MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311018259.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-11-18
Estimated Expiration
2043-08-14

AI Technical Summary

Technical Problem

The existing technology for molding expanded polypropylene (EPP) beads suffers from long molding cycles and high energy consumption.

Method used

By introducing a reinforcing agent containing polytetrafluoroethylene (PTFE) into foamed polypropylene beads, the PTFE forms physical entanglement inside the EPP, reducing the cooling time during the molding process and shortening the molding cycle.

Benefits of technology

While ensuring the excellent resilience of EPP, it effectively reduces molding energy consumption and molding cycle, and improves the appearance quality and mechanical properties of molded parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a foamed polypropylene bead and a molded part thereof, and relates to the technical field of foamed polypropylene; the foamed polypropylene bead is prepared from composite particles through a kettle foaming method; the composite particles comprise a core layer and a skin layer wrapped outside the core layer; the core layer comprises a reinforcing aid; the reinforcing aid is a composite material containing PTFE and polypropylene A. The foamed polypropylene bead provided by the application introduces the reinforcing aid containing PTFE and polypropylene A into the core layer, utilizes the effect of in-situ fiberization of PTFE in the polypropylene A matrix and the formation of mutual entanglement, thereby forming a physical entanglement effect in the EPP through the reinforcing aid, improving the melt strength of the EPP, facilitating the formation of a closed-cell structure of the foamed bead, and improving the mechanical properties; meanwhile, in the molding process, another effect of the entanglement effect is to inhibit the excessive expansion of the EPP material in the mold cavity, shorten the cooling time, and thus shorten the molding cycle.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of foamed polypropylene, in particular to a foamed polypropylene bead and a molded part thereof. BACKGROUND

[0002] Foamed polypropylene (EPP) beads and molded parts thereof are light in weight, excellent in mechanical properties, and easy to be made into various special-shaped structures, and have been widely used in the fields of automobile parts, turnover packaging, cushion packaging, light household, children's entertainment, etc.

[0003] Common foamed polypropylene parts are mostly formed by steam molding of EPP beads, and the molding process usually takes a long time and consumes a large amount of steam energy. With the increasing demand for EPP applications, EPP molding processing users have more specific requirements for low molding energy consumption and high processing efficiency of EPP, i.e. lower steam pressure in the EPP steam molding process and shorter time for producing EPP parts by a single mold.

[0004] Therefore, it is urgent to provide a foamed polypropylene bead with a short molding cycle. SUMMARY

[0005] The technical problem to be solved by the present application is that the molding cycle of the EPP bead in the prior art is long. The present application provides a foamed polypropylene bead, which introduces a reinforcing additive containing polytetrafluoroethylene (PTFE) to form physical entanglement inside the EPP by using PTFE, reduce the cooling time in the molding process, shorten the molding cycle, and solve the problem of long molding cycle of the EPP bead in the prior art.

[0006] The technical solution adopted by the present application to solve the technical problem is:

[0007] A foamed polypropylene bead is prepared by a kettle foaming method using composite particles.

[0008] The composite particles comprise a core layer and a skin layer coated on the outside of the core layer.

[0009] The core layer comprises the following components by weight fraction:

[0010] Polypropylene A 80-95 parts;

[0011] Reinforcing additive 5-20 parts;

[0012] Cell nucleating agent 0-0.1 parts;

[0013] The skin layer comprises the following components by weight fraction:

[0014] Polyethylene C 40-75 parts;

[0015] Polypropylene A 20-50 parts;

[0016] Ethylene-acrylic acid copolymer 5-15 parts;

[0017] The reinforcing aid is a composite material containing PTFE and polypropylene A.

[0018] Optionally, the reinforcing aid is prepared by the following method:

[0019] S01: mixing PTFE powder, polypropylene A and white oil to obtain a mixture;

[0020] S02: mixing the mixture in a 180℃ internal mixer for 5-10 minutes to obtain a mixed material;

[0021] S03: granulating the mixed material by double screw extrusion to obtain the reinforcing aid.

[0022] Optionally, the average particle size of the PTFE powder is 1-10μm.

[0023] Optionally, the mass ratio of the PTFE powder, the polypropylene A and the white oil in step S01 is 5:94:1.

[0024] Optionally, the mass ratio of the core layer to the skin layer is (90-97):(3-10).

[0025] Optionally, the polypropylene A is a random copolymer polypropylene with a melt index of 6-9g / 10min and a melting point of 137℃-150℃.

[0026] Optionally, the melting point of the polypropylene A is 138℃-148℃.

[0027] Optionally, the melt index of the polyethylene C is 4-15g / 10min and the melting point is 105℃-125℃.

[0028] Optionally, the melt index of the ethylene-acrylic acid copolymer is 5-10g / 10min and the mass content of acrylic acid is 5-15%.

[0029] Another object of the present application is to provide a molded part obtained by steam molding the foamed polypropylene beads as described above.

[0030] The present application has the following advantages:

[0031] The foamed polypropylene beads provided by the application introduce a reinforcing aid containing PTFE and polypropylene A in the core layer, utilize the in-situ fiberization and intertangling effect of PTFE in the polypropylene A matrix, thereby form a physical intertangling effect in the EPP by the reinforcing aid, improve the melt strength of the EPP, facilitate the foamed beads to form a closed-cell structure, and improve the mechanical properties; meanwhile, in the molding process, the other effect of the intertangling effect is to inhibit the excessive expansion of the EPP material in the mold cavity, shorten the cooling time, and thereby shorten the molding cycle. DETAILED DESCRIPTION

[0032] The application will be further described in detail. The examples described below are exemplary and are intended to explain the application, and cannot be understood as a limitation of the application, and all other examples obtained by those skilled in the art on the basis of the examples of the application without creative labor belong to the scope of protection of the application.

[0033] To solve the problem of long molding cycle of the EPP beads in the molding process in the prior art, the application provides foamed polypropylene beads, which are prepared by a kettle foaming method from composite particles; wherein the composite particles comprise a core layer and a skin layer coated on the outside of the core layer.

[0034] The core layer comprises the following components according to weight fractions:

[0035] Polypropylene A 80-95 parts;

[0036] Reinforcing aid 5-20 parts;

[0037] Cell nucleating agent 0-0.1 part;

[0038] The skin layer comprises the following components according to weight fractions:

[0039] Polyethylene C 40-75 parts;

[0040] Polypropylene A 20-50 parts;

[0041] Ethylene-acrylic acid copolymer 5-15 parts;

[0042] The reinforcing aid is a composite material containing PTFE and polypropylene A.

[0043] The foamed polypropylene beads provided by the application have a structure of a foamed core layer coated by a non-foamed skin layer; the reinforcing aid containing PTFE and polypropylene A is introduced into the core layer, the in-situ fiberization of PTFE in the polypropylene A matrix and the effect of forming mutual entanglement are utilized, so that the physical entanglement effect is formed in the EPP by the reinforcing aid, the melt strength of the EPP is improved, the closed cell structure of the foamed beads is beneficial to form, and the mechanical properties are improved; meanwhile, in the process of molding and molding, the other effect of the entanglement effect is to inhibit the excessive expansion of the EPP material in the mold cavity, so as to shorten the cooling time and thus shorten the molding cycle.

[0044] When the addition amount of the reinforcing aid in the core layer is less than 5 parts by weight, the physical reinforcing effect is weak; when the addition amount is more than 20 parts by weight, the molding expansion of the EPP in the molding process is excessively inhibited, the appearance quality of the product is poor, and the molding energy consumption is increased.

[0045] At present, in view of the long molding cycle of the EPP beads, the prior art records that a certain proportion of oxides, inorganic salt water absorbents and inorganic mineral powders are added in the formula, so as to achieve the effect of reducing the molding energy consumption and cycle of the EPP; however, a large amount of inorganic substances are added, so as to reduce the resilience of the EPP and affect the packaging cushioning performance; and this technology does not involve the molding of super-light EPP with a density of less than 30 g / L; the foamed polypropylene beads provided by the application can effectively reduce the molding energy consumption and cycle of the EPP, while ensuring excellent resilience of the EPP, and the foamed polypropylene beads provided by the application can be used for the molding of super-light EPP with a density of less than 30 g / L.

[0046] Specifically, the preparation method of the reinforcing aid is as follows:

[0047] S01: uniformly mechanically mixing PTFE powder, polypropylene A and white oil to obtain a mixture;

[0048] S02: mixing the mixture in a banbury mixer at 180 DEG C for 5-10 min to obtain a mixed material; preferably, the rotor speed of the banbury mixer is 200 rpm;

[0049] S03: granulating the mixed material by a double screw extruder to obtain the reinforcing aid; preferably, the weight of a single particle of the reinforcing aid is 20-30 mg; preferably, the processing temperature of the double screw is 180 DEG C-200 DEG C, and the rotation speed of the double screw is 200 rpm.

[0050] The application introduces the reinforcing aid into the system by a composite material mode with PTFE powder and polypropylene A as raw materials, so as to ensure the in-situ fiberization of PTFE in the polypropylene A matrix and improve the effect of mutual physical entanglement, so as to further reduce the molding energy consumption of the EPP and shorten the molding cycle while ensuring the resilience of the EPP.

[0051] The processing temperature in the present application is higher than the softening temperature of PTFE and lower than 200 DEG C, so that the fiberized entanglement effect in the reinforcing aid will not disappear due to excessive heat shrinkage, thereby ensuring the stability of the structure and the durability of the effect.

[0052] Further, the average particle size of the PTFE powder is preferably in the range of 1-10 μm; and the mass ratio of the PTFE powder, the polypropylene A and the white oil in step S01 is preferably 5:94:1.

[0053] The composite microparticle in the present application adopts the structure of core layer coated by skin layer, and the mass ratio of the core layer to the skin layer is preferably (90-97):(3-10).

[0054] The polypropylene A is preferably random copolymerized polypropylene, and the melt index is in the range of 6-9 g / 10 min, and the melting point is in the range of 137 DEG C-150 DEG C, and the melting point is further preferably in the range of 138 DEG C-148 DEG C; and the melt index of the polyethylene C is preferably in the range of 4-15 g / 10 min, and the melting point is in the range of 105 DEG C-125 DEG C.

[0055] In order to improve the stability of the material extrusion process, the ethylene-acrylic acid copolymer is introduced into the unfoamed skin layer, and the melt index of the ethylene-acrylic acid copolymer in the unfoamed skin layer is preferably in the range of 5-10 g / 10 min, and the mass content of the acrylic acid in the ethylene-acrylic acid copolymer is in the range of 5-15%.

[0056] In addition, the average particle size of the cell nucleating agent is preferably in the range of 3-10 μm; and the cell nucleating agent is preferably selected from at least one of zinc borate, talc, barium sulfate, calcium carbonate, calcium stearate and silicon dioxide.

[0057] The composite microparticle provided by the present application can further comprise other commonly used plastic aids such as antioxidants, lubricants, antistatic agents, flame retardants and colorants according to the needs.

[0058] The preparation process of the composite microparticle is preferably as follows:

[0059] According to the formula amount, the core layer material and the skin layer material are respectively added into the core layer double-screw extruder and the skin layer double-screw extruder of the double-screw co-extruder set, and then the plasticized materials are simultaneously extruded into filaments through the co-extrusion die to obtain the composite microparticle with the skin layer coated on the core layer; and the temperature of the core layer double-screw extruder and the skin layer double-screw extruder is in the range of 180 DEG C-200 DEG C. The average length of the composite microparticle is preferably in the range of 1.5-2.8 mm, and the average single particle weight is in the range of 0.5-1.8 mg.

[0060] The composite microparticles in the application adopt a skin layer covering a core layer structure, and the specific resin formula of the skin layer endows the foamed bead skin with the characteristics of easy sintering and not easy to stick to the mold; when the addition amount of low-melting-point polyethylene of the skin layer resin is higher than 75 parts, it is more beneficial to sinter the bead skin and reduce the molding energy consumption, but there is a risk of sticking to the mold during the steam molding process; when the addition amount of polyethylene of the skin layer resin is lower than 40 parts, it is not conducive to reducing the sintering energy consumption of the bead skin; when the addition amount of polypropylene A of the skin layer resin is higher than 50 parts, it is not conducive to reducing the sintering energy consumption of the bead skin; when the addition amount of polypropylene A of the skin layer resin is lower than 20 parts, it is more beneficial to sinter the bead skin and reduce the molding energy consumption, but there is a risk of sticking to the mold during the steam molding process.

[0061] Another object of the application is to provide a preparation method of the foamed polypropylene bead as described above, which comprises the following steps:

[0062] S1: the composite microparticles, a dispersing agent and water are added to an autoclave, CO2 is added after sealing, stirring is not stopped, the temperature of the reaction kettle is raised to a foaming temperature of 140-155 DEG C, the pressure in the kettle is adjusted to a foaming pressure of 3-4 MPa, the temperature and pressure conditions are maintained for 5-30 min, the material is discharged to atmospheric pressure after pressure relief, and primary foamed polypropylene beads are obtained; the bulk density of the primary foamed polypropylene beads is 30-35 g / L, the melting peak enthalpy value of the first DSC melting curve higher than the inherent melting point is 14-22 J / g (hereinafter referred to as the high-temperature melting peak enthalpy value); wherein the dispersing agent is kaolin, and the mass ratio of the composite microparticles, the dispersing agent and water is 100:(0.03-1):(100-200);

[0063] S2: the primary foamed polypropylene beads are incubated at room temperature for 12-24 h, sealed in a pre-pressing tank, and loaded with air at a pressure of 0.35-0.8 MPa for 15-30 h, and the primary foamed polypropylene beads after pressure loading are heated and expanded in a flow channel foaming pipeline at a normal pressure at 85-110 DEG C, to form secondary foamed beads with a smaller bulk density, i.e. foamed polypropylene beads, and the bulk density of the foamed polypropylene beads is 15-29 g / L.

[0064] It should be noted that the foamed polypropylene beads provided by the application can be prepared by primary foaming, or can be prepared by secondary foaming, and the specific preparation method can be determined according to the requirements for the density and other properties of the foamed beads.

[0065] The application provides a preparation method of foamed polypropylene beads, and the prepared foamed polypropylene beads have a structure of a foamed core layer coated with a non-foamed skin layer; a reinforcing aid containing PTFE and polypropylene A is introduced into the core layer, the PTFE is in-situ fiberized in the polypropylene A matrix and forms an effect of mutual entanglement, so that the reinforcing aid forms a physical entanglement effect in the EPP, the melt strength of the EPP is improved, the foamed beads are beneficial to forming a closed cell structure, and the mechanical properties are improved; meanwhile, in the molding process, the other effect of the entanglement effect is to inhibit the excessive expansion of the EPP material in the mold cavity, so that the cooling time is shortened, and the molding cycle is shortened.

[0066] In the preparation process, the bulk density of the primary foamed beads obtained by tank pressure foaming is 30-35 g / L, and the high-temperature melting endothermic enthalpy value is 14-22 J / g; and the primary foamed beads are subjected to atmospheric secondary foaming to obtain secondary foamed beads with a bulk density of 15-29 g / L; the 15-35 g / L ultra-light EPP beads prepared by the foaming process parameters have thin cell walls, and the molding cycle is greatly shortened. When the density of the primary foamed beads is lower than 30 g / L, the closed cell structure of the foamed beads is easily damaged, if the beads are used for secondary foaming to obtain beads products with lighter density, the defect of closed cell damage will be further enlarged, although the molding cycle is reduced, but the appearance quality of the molded parts is poor, the resilience is reduced, and the compression resistance is reduced; when the density of the primary foamed beads is higher than 35 g / L, if the beads are used for secondary foaming to obtain beads products with lighter density, the trend of cycle reduction in the molding process will be weakened. When the high-temperature melting endothermic enthalpy value of the primary foamed beads is lower than 14 J / g, the closed cell structure of the beads is easily damaged, the appearance quality of the molded parts is poor, the resilience is reduced, and the compression resistance is reduced; when the high-temperature melting endothermic enthalpy value of the primary foamed beads is higher than 22 J / g, the expansion property of the beads in the molding process is poor, and the appearance quality of the molded parts is poor.

[0067] The foamed polypropylene beads provided by the application have the characteristics of low molding energy consumption, short single-mold molding cycle, excellent appearance quality of molded parts, excellent resilience and excellent compression resistance.

[0068] Another purpose of the application is to provide a molded part, which is obtained by steam molding of the foamed polypropylene beads as described above.

[0069] In order to make the above-mentioned purposes, characteristics and advantages of the application more obvious and easy to understand, the specific embodiments of the application are described in detail below.

[0070] Unless otherwise specified, the melt index of the ethylene-acrylic acid copolymer in the embodiments and comparative examples of the present invention is 7.5 g / 10 min, the mass content of acrylic acid in the ethylene-acrylic acid copolymer is 10%, the average particle size of the cell nucleating agent is 3 micrometers, the cell nucleating agent is silica, the dispersant is kaolin, and the mass ratio of PTFE powder, polypropylene A and white oil in the reinforcing additive is 5:94:1.

[0071] The performance parameters of the materials selected for other experiments are shown in Table 1.

[0072] Table 1

[0073]

[0074]

[0075] The formulations and parameters of composite microparticles S1-S5 and composite microparticles D1-D9 are shown in Table 2.

[0076] Table 2

[0077]

[0078] Foamed beads were prepared using composite microparticles S1-S5 and microparticles D1-D9, and then molded parts were prepared using the foamed beads. The parameters and properties of the molded parts during the preparation process of Examples 1-7 and Comparative Examples 1-10 are shown in Table 3.

[0079] Table 3

[0080]

[0081]

[0082] Among them, the minimum molding pressure is the minimum steam sintering pressure required for the proportion of particles whose cell structure is destroyed on the fracture surface of the foamed bead molded part to be above 95%.

[0083] Surface quality of the part: "i" indicates that there are many pits or gaps on the surface of the part; "ii" indicates that there are few pits or gaps on the surface of the part; "iii" indicates that there are no pits or gaps or very few or very small pits or gaps on the surface of the part.

[0084] Does it stick to the mold? "□" indicates that the part frequently sticks to the mold surface, making demolding difficult, or the sticking rate is not less than 10%, meaning that in 100 molding cycles, the part sticks to the mold at least 10 times; "□" indicates that sticking occurs occasionally, or the sticking rate is greater than 1% and less than 10%, meaning that in 100 molding cycles, the number of sticking occurrences is between 1 and 10 times. This indicates that the material is basically non-sticky, or the sticking rate is less than 1%, meaning that out of 100 molding cycles, sticking occurs at most once or not at all.

[0085] molding:

[0086] 1. The EPP beads to be formed need to go through a pressure loading step in a sealed pre-pressing tank; according to the bulk density of the EPP beads to be formed, the pre-pressing tank pressure loading pressure is 0.1-0.5 MPa, and the pressure loading time is not less than 8 h, generally the lower the bulk density of the EPP beads to be formed, the higher the pressure loading pressure;

[0087] 2. After the pressure loading of the EPP beads, the EPP beads are filled in a metal mold (the internal cavity is a cuboid with a length of 460 mm, a width of 350 mm, and a thickness of 50 mm), and after molding and sintering by high-temperature water vapor with a certain pressure, the sintered product in the mold is cooled and shaped by vacuum pumping and cooling water, then the mold is opened, and the product is ejected from the mold, which is called demolding; the total time of a complete molding process, i.e. the time for completing one molding product on the molding machine, is called the molding cycle; if the product sticks to the mold, it means that the product skin sticks to the mold contact surface during the last step of demolding and cannot be effectively ejected, which needs to be manually removed, seriously affecting the molding efficiency; in this embodiment, the molding water vapor pressure value and cooling water time of each example are adjusted according to the situation, and other parameters including the filling mold time, water vapor heating time, and vacuum pumping time are consistent parameters.

[0088] 3. After the product is demolded, it is placed in a hot air oven at 80°C for 8 h to fully dry the moisture inside and outside the product and fix the final structure of the molded product.

[0089] The final product after the baking treatment has a length L and a width B; in this example, the length shrinkage rate is [(460-L) / 460]*100%, and the width shrinkage rate is [(350-B) / 350]*100%, and the average of the length shrinkage rate and the width shrinkage rate is selected as the average shrinkage rate.

[0090] The comparison of the molding cycles of different examples needs to be under the condition that the foaming bead foaming ratio, the molded product foaming ratio, and the average shrinkage rate are consistent. In view of the specific situation of the industry product, the EPP beads with the same foaming ratio in the industry, i.e. the difference in the bulk density of the foaming beads is not more than 5 g / L, preferably not more than 4 g / L, and most preferably not more than 3 g / L; the molded products with the same foaming ratio, i.e. the difference in the apparent density of the molded products is not more than 3 g / L; the average shrinkage rates are the same, i.e. the difference in the average shrinkage rate is not more than 0.2%; the shorter the molding cycle in this example, the shorter the cooling water time in the foaming bead molding process.

[0091] Compared with Example 3, in Comparative Example 1, the weight fraction of the core layer reinforcing aid is less than 5 parts, which is insufficient for physically reinforcing the material and cannot effectively inhibit the excessive expansion of the foamed bead during the molding process, resulting in a long molding cycle; the insufficient physical reinforcement also causes the closed cell structure to have a tendency to deteriorate during the primary foaming process, which further amplifies this disadvantage during the secondary foaming process, so that the molded part of the secondary foamed beads has a small number of pits on the surface and the compressive stress at 50% strain is reduced.

[0092] Compared with Example 5, in Comparative Example 2, the weight fraction of the core layer reinforcing aid is more than 20 parts, which excessively enhances the strength and elasticity of the material and excessively inhibits the expansion of the foamed bead during the molding process, although this helps to shorten the molding cycle, but the molded part has a small number of sintering marks of the beads on the surface.

[0093] Compared with Example 7, in Comparative Example 3, the skin layer does not contain low-melting-point polyethylene C, so the molding energy consumption is high, the relatively high molding pressure leads to a longer water cooling and setting time during the molding process, i.e., a longer molding cycle; and the relatively high steam pressure during the molding process relatively more destructively affects the closed cell structure, resulting in a small number of pits on the surface of the molded part and a reduced compressive stress at 50% strain.

[0094] Compared with Example 7, in Comparative Example 4, the skin layer does not contain polypropylene A, although the molding energy consumption is low, but the low-melting-point polyethylene C in the skin layer is prone to excessive melting during the molding process, occasionally causing the molded part to stick to the mold.

[0095] Compared with Example 1, in Comparative Example 5, the core layer does not contain a reinforcing aid, which lacks physical reinforcement and cannot effectively inhibit the excessive expansion of the foamed bead during the molding process, resulting in a long molding cycle; the lack of physical reinforcement also causes the closed cell structure to have a tendency to deteriorate during the primary foaming process, so that the molded part has a small number of pits on the surface and the compressive stress at 50% strain is reduced.

[0096] Compared with Example 3, in Comparative Example 6, the bulk density of the primary foamed beads is controlled to be 49 g / L through process conditions, and then the secondary foamed beads with a density of 16 g / L are obtained through the secondary foaming process; the molding cycle of the secondary foamed beads is significantly lengthened, and the effect of shortening the molding cycle of the present application cannot be achieved.

[0097] Comparative Example 7 uses polypropylene A3 resin which is not in the technical specification range, and its physical properties are not suitable for the existing bead foaming process. It is repeatedly tested in the high temperature and pressure autoclave foaming process range of the present technology, and it is impossible to obtain once foamed beads with a bulk density of 30-35 g / L. In Comparative Example 7, the material cannot effectively expand when the foaming temperature is low. When the foaming temperature reaches the expandable condition, the viscosity and elasticity of the material as a whole are seriously insufficient, and the foamed beads cannot effectively wrap the gas. The surface of the foamed beads is wrinkled and the volume is uneven, and it is impossible to stably obtain once foamed polypropylene beads with controllable bulk density that can be used for subsequent secondary foaming or molding.

[0098] Comparative Example 8, compared with Example 1, uses zinc borate powder instead of PTFE in the reinforcing aid, and cannot form network entanglement, lacks physical reinforcing effect, and cannot effectively inhibit the excessive expansion of the foamed beads during the molding process, resulting in a long molding cycle. The lack of physical reinforcing effect also causes the closed cell structure to have a tendency to deteriorate during the once foaming process, so a small amount of pits appear on the surface of the molded part, and the compressive stress decreases at a strain of 50%.

[0099] Comparative Example 9, compared with Example 1, uses glass fiber powder instead of PTFE in the reinforcing aid, and cannot form network entanglement, lacks physical reinforcing effect, and cannot effectively inhibit the excessive expansion of the foamed beads during the molding process, resulting in a long molding cycle. The lack of physical reinforcing effect also causes the closed cell structure to have a tendency to deteriorate during the once foaming process, so a small amount of pits appear on the surface of the molded part, and the compressive stress decreases at a strain of 50%.

[0100] Comparative Example 10, compared with Example 1, directly adds PTFE powder, which has not undergone the in-situ fiberization process of the internal mixer. Although the PTFE powder receives a certain shearing action during the double screw particle formation process, some PTFE may form a fiber structure, but the shearing time is short and the shearing strength is low, and the PTFE cannot effectively form an in-situ fiberization network structure in the matrix, so the physical reinforcing effect is still not obvious, and it is impossible to effectively inhibit the excessive expansion of the foamed beads during the molding process, resulting in a long molding cycle. The lack of physical reinforcing effect also causes the closed cell structure to have a tendency to deteriorate during the once foaming process, so a small amount of pits appear on the surface of the molded part, and the compressive stress decreases at a strain of 50%.

[0101] Based on the above ideal embodiments according to the present application, through the above description, relevant personnel can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the contents of the specification, and must be determined by the scope of the claims.

Claims

1. A type of foamed polypropylene beads, characterized in that, The foamed polypropylene beads are prepared from composite microparticles by a batch foaming method; The composite microparticles include a core layer and a skin layer covering the outside of the core layer; The core layer comprises the following components in parts by weight: Polypropylene A 80-95 parts; 5-20 parts of reinforcing agent; 0-0.1 parts of bubble nucleating agent; The dermis comprises the following components in parts by weight: Polyethylene C 40-75 parts; Polypropylene A 20-50 parts; 5-15 parts of ethylene-acrylic acid copolymer; The reinforcing agent is a composite material containing PTFE and polypropylene A; The preparation method of the reinforcing agent is as follows: S01: Mix PTFE powder, polypropylene A and white oil to obtain a mixture; S02: The mixture is mixed in a mixer at 180°C for 5-10 minutes to obtain the mixed material; S03: The internally mixed material is granulated by twin-screw extrusion to obtain the reinforcing agent; The mass ratio of the PTFE powder, the polypropylene A, and the white oil in step S01 is 5:94:1; The polypropylene A is a random copolymer polypropylene with a melt index ranging from 6 to 9 g / 10 min and a melting point of 137°C to 150°C.

2. The foamed polypropylene beads as described in claim 1, characterized in that, The average particle size of the PTFE powder ranges from 1 to 10 μm.

3. The foamed polypropylene beads as described in claim 1 or 2, characterized in that, The mass ratio of the core layer to the skin layer is (90-97):(3-10).

4. The foamed polypropylene beads as described in claim 1, characterized in that, The melting point of the polypropylene A is 138℃-148℃.

5. The foamed polypropylene beads as described in claim 1 or 2, characterized in that, The polyethylene C has a melt index of 4-15 g / 10 min and a melting point of 105℃-125℃.

6. The foamed polypropylene beads as described in claim 1 or 2, characterized in that, The ethylene-acrylic acid copolymer has a melt index of 5-10 g / 10 min and an acrylic acid mass content of 5-15%.

7. A molded part, characterized in that, It is obtained by steam molding of foamed polypropylene beads as described in any one of claims 1-6.

Citation Information

Patent Citations

  • Method for microcellular injection molding of open-cell polymer foam material and product

    CN111286117A

  • Energy-saving foamed polypropylene bead and molded part thereof

    CN113956530A